Synthesis, Characterization and Antibacterial Activity of Rice Husk Biochar/MnFe2O4 Nanocomposites - Oka Yana Afrizki; Poedji Loekitowati Hariani; Nabila Aprianti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2026)
The increasing contamination with microorganisms has driven the development of effective, environmentally friendly antibacterial materials. Biochar was used as a porous matrix to support the dispersion of MnFe₂O₄ particles and to enhance the material's surface area. This study aims to synthesize a rice husk–based biochar/MnFe₂O₄ composite and evaluate its structural and morphological characteristics, as well as antibacterial activity. The composite was synthesized by coprecipitation and characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy–Energy Dispersive X-ray Spectroscopy (SEM–EDX), and Fourier Transform Infrared Spectroscopy (FTIR). Antibacterial activity was evaluated using the disk diffusion method against Escherichia coli (Gram-negative) and Staphylococcus aureus (Gram-positive) at concentration variations of 1000–5000 mg/L. XRD results confirmed the formation of a spinel MnFe₂O₄ phase, as indicated high-intensity diffraction peaks   at 31.56° and 35.22° and the average crystallite size calculated using the Scherrer equation was approximately 27.1 nm, indicating the formation of nanocrystalline domains. SEM analysis revealed that MnFe₂O₄ nanoparticles were uniformly dispersed on the biochar surface, while EDX confirmed the presence of C, O, Mn, and Fe elements. FTIR analysis identified –OH, C=O, and C–O functional groups, along with characteristic Mn–O and Fe–O vibrations, confirming successful composite formation. Antibacterial activity increased with concentration, reaching a maximum inhibition zone of 7.2 mm against both E. coli and S. aureus at 5000 mg/L, indicating mild antibacterial performance. The composite exhibits eco-friendly characteristics due to its biomass-derived biochar matrix and offers magnetic separability, facilitating easy recovery and potential reuse for sustainable environmental applications.Keywords: Rice husk biochar, MnFe₂O₄, antibacterial activity